Eat, play, view, sleep: Exploring Mexican American mothers' perceptions of decision making for four behaviors associated with childhood obesity risk. (1st June 2016) - Davis, Rachel E.; Cole, Suzanne M.; Blake, Christine E.; McKenney-Shubert, Shannon J.; Peterson, Karen E.
Abstract: Objective: This mixed methods study sought to understand who makes decisions about whether preschool-aged Mexican American children engage in eating, outdoor play, sleep, and screen time behaviors. Methods: Forty Mexican American mothers of children ages 3–4 participated in two interviews, during which both closed- and open-ended questions elicited perceptions of who made decisions for the four behaviors, as well as who was present, mealtime rules, and food choice values. Interviews were transcribed, coded for emergent themes, and compared across participants. Results: Participants generally perceived themselves to be primary decision makers for all four behaviors; however, food decisions often seemed to be made collaboratively with the child. Fathers were most likely to participate in evening television decisions. Other family members were rarely mentioned. Selecting foods that children liked was a strong food choice value, while cost was rarely mentioned. Participants appeared to have low perceived control over their child's behaviors relative to their perceived roles in decision making. Conclusions: Mothers may be the primary audience for obesity prevention messages for preschool-aged, Mexican American children; however, health promotion programs may need to increase mothers' awareness of their control over children's behaviors. Understanding how children's behaviors are regulated is an important aspect of obesity prevention for low-income, Mexican American children.